Anti-E Alloimmunization: A Rare Cause of Severe Fetal Hemolytic Disease Resulting in Pregnancy Loss - An-Shine Chao; Angel Chao; Szu Ying Ho; Yao-Lung Chang; Reyin Lien (Case Reports in Medicine)
We report a case of severe intrauterine hemolysis caused by sole anti-E alloimmunization. A 36-year-old multipara woman presented with hydrops fetalis at 27 weeks of gestation. She had a history of previous neonatal death. In this pregnancy, she was found to have very high titer of anti-E antibody. Ultrasonography detected marked skin edema, cardiomegaly, hepatosplenomegaly, pleural effusion, ascites, placentomegaly, and polyhydramnios. The Doppler peak systolic velocity in the middle cerebral artery was 0.8 m/s, indicating severe fetal anemia. Multiple intrauterine transfusions for the anemic fetus were administered. However, persistent severe fetal anemia and placentomegaly caused poor neonatal death and mirror syndrome in the mother. Uncommon red blood cell alloimmunization has to be watched for early in any population, especially in a woman with a history of unexplained perinatal loss.